Pengaruh Penggunaan Aplikasi E-Office dan Sistem Tata Kelola Persuratan Terhadap Efektivitas Kerja Pegawai Injourney Tourism Development Corporation (ITDC) - Swandewi, Ni Kadek Santhi; Suciani, Ni Ketut; Artatanaya, I Gusti Lanang Suta (CV. Lenggogeni Data Publishing, 2025)
This study aims to determine the effect of the use of e-office applications and a correspondence management system on employee work effectiveness at InJourney Tourism Development Corporation (ITDC). The background of this study is based on the importance of digital transformation in office administration management to improve efficiency, transparency, and work productivity. The research method used was quantitative, with a survey approach using a questionnaire distributed to 108 respondents, who were ITDC employees. The independent variables in this study were the use of e-office applications and the correspondence management system, while the dependent variable was employee work effectiveness. The analysis results indicate that partially, the use of e-office applications had a significant effect on employee work effectiveness, while the correspondence management system did not have a significant effect individually. However, simultaneously, both variables had a positive and significant effect on employee work effectiveness. These findings indicate that optimizing the application of information technology through e-office, supported by good correspondence management, can improve employee performance in a public service-based organization like Injourney Tourism Development (ITDC).